FLOW OF A VISCOUS GAS IN A DIFFUSER CHANNEL WITH TURBULATORS - Терещенко, Ю. М.; Дорошенко, К. В.; Терещенко, Ю. Ю.; Гамзег, П. (Science-based technologies, 2017)
A calculation series of flow in smooth diffusers with an opening angle α = 6 ... 40º was carried out. Turbulent separated flows were calculated using the averaged Navier-Stokes equations with the turbulence model SST. The results of flow numerical simulation in smooth diffusers have shown that at α> 20º there is a flow separation, which is accompanied by the formation of a back-circulation flow in the form of vortices. The energy losses increase with increasing of the angle o f the diffuser opening. The paper presents the results of a study of the effect of the density of the accommodation of turbulators in a diffuser channel with a large opening angle of the diffuser at Mach number M = 0.5. The characteristics of the diffusers were studied at a turbulator density coefficient of 0.5; 0.25; 0.125. The use of turbulators at the entrance section of the diffuser channel with a density coefficient of 0.125 ... 0.5 resulted in a decreasing of the value of the total pressure loss coefficient from 0.3 to 0.19 ... 0.22.